PELATIHAN BANTUAN HIDUP DASAR (BHD) PADA KARYAWAN CLEANING SERVICE DI GENDUNG STUDENT CENTER POLITEKNIK NEGERI INDRAMAYU - Niken Wulan Hasthi Murti; Suci Nurjanah; Berlian Kusuma Dewi (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
Abstract Accidents can occur, if not handled properly will cause a heart attack. The incidence of cardiac arrest can occur at any time. The rate of cardiac events ranges from 10 events from 100,000 normal people under 35 years and annually reaches around 300,000-350,000 events. This can cause an emergency that requires help in the form of basic life support, emergency events if not handled properly can cause death. Life support techniques are important for the general public to know, especially employees around academic centers. Indramayu State Polytechnic is an educational institution which is one of the places that has the risk of accidents and heart attacks because at the Polytechnic students, lecturers, academics carry out various activities, the health conditions of each individual vary, so it is possible to obtain basic life support. The purpose of counseling and training on Basic Life Support for the civitas in the Student Center environment is to improve the knowledge and skills of good basic life support by the community who carry out activities in the Student Center Building or nearby, this training will be carried out directly so that employees are skilled in providing assistance. basic life. Method: descriptive with cross sectional approach. The result of this community service is that there is an increase in knowledge before and before being given basic life support training for cleaning service employees at the Indramayu State Polytechnic. Conclusion: basic life support measures taken by people who are around the patient immediately after the incident can improve the patient's life. Therefore, it is recommended for health institutions to carry out community service or counseling to the wider community how to carry out basic life support. Keywords: Basic Life Support, Cardiac Arrest, community, heart disease